Ulnar nerve reconstruction with a basilic vein tributary graft: a practical and easily replicable technique with favourable outcomes - Kim, Collin Looi Seng; Md Yusoff, Zuhri; Arumugam, Manohar; Liew, Siew Khei; Mohamed Saaid, Firdati (Universiti Putra Malaysia Press, 2024)
A young gentleman presented with a closed fracture of the left radius and an open fracture of the left ulna complicated with segmental loss of the ulnar nerve measuring 1.5cm. After thorough debridement and stabilization of the bone injuries, the ulnar nerve gap was bridged with an autologous venous graft harvested off a tributary of the basilic vein that served as a nerve conduit. At 18 months post-surgery, sensori-motor function of the patient’s left ulnar nerve was nearly fully restored, indicative of successful reconstitution of the ulnar nerve using a basilic vein tributary vein graft.